Pelatihan Pembuatan Website Pelaporan Tracer Study untuk Mendukung Akreditasi Program Studi pada UKI Toraja - Poerwanto, Bobby; Ismail, Asri (Insan Kreasi Media, 2023)
Tracer study is one of the instruments used to obtain data related to alumni when they are graduated, during the transition period, and during the period when tracking is carried out. The data from the tracer study is not only to get an overview of the condition of alumni, it is also used to provide data on accreditation needs at both BAN PT and LAMs. The problems that partners have are that the implementation of tracer studies is not yet standardized and there is also no tracer study information system website available that assists the implementation, processing and reporting of tracer studies. These problems are the goal of implementing this service activity. To solve this problem, there were 2 main activities carried out, namely assistance in making a tracer study website which was carried out for 1 month, and training in processing and reporting tracer study data at the Ministry of Education and Culture which was carried out on March 25, 2023. The first result of this activity was the availability of a website tracer study which has accommodated UKI Toraja's tracer study needs, and increased knowledge related to tracer study implementation standards to maximize value in study program accreditation